Changes in the neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios before and after percutaneous coronary intervention and their impact on the prognosis of patients with acute coronary syndrome (Clinics, 2021)
OBJECTIVES: This study aimed to prospectively observe the changes in the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) before and after percutaneous coronary intervention (PCI) and their impact on the prognosis of patients with acute coronary syndrome (ACS). METHODS: Blood samples from 205 patients with ACS were collected at admission and at 24h and 30 days postPCI to observe changes in the complete blood count. The Cox multivariate regression model was used to analyze the factors influencing major adverse cardiac events (MACE) after PCI in patients with ACS. A receiver operating characteristic (ROC) curve was used to evaluate the predictive value of inflammation indicators for MACE after PCI. RESULTS: Following PCI, NLR and PLR first increased postoperatively and then decreased within 30 days after PCI. Cox multivariate regression analysis showed that NLR and PLR at 24h post-PCI and acute ST-segment elevation myocardial infarction were independent influencing factors for the incidence of MACE after PCI. The ROC curve analysis showed that the NLR at 24h post-PCI was a better predictor of the incidence of MACE. The NLR at 24h post-PCI was significantly correlated with the number and length of implanted stents and operation duration. CONCLUSIONS: After PCI, patients with ACS had an increased neutrophil proportion and NLR. The NLR at 24h post-PCI was a better predictor of the incidence of postoperative MACE.